Self-Medication with NSAIDs in Gondar city: prevalence, predictors, and public health implications - Wondim Ayenew; Addisu Afrassa Tegegne; Gebremariam Genet; Liknaw Workie Limenh; Lamrot Yohannes; Abdulwase Mohammed Seid; Tekletsadik Tekleslassie Alemayehu; Wudneh Simegn (Scientific Reports)
Abstract Self-medication with Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) is prevalent, particularly for pain and fever management. However, this practice poses significant public health risks, including gastrointestinal complications, renal impairment, and cardiovascular events. Therefore, this study aimed to assess the prevalence of self-medication with NSAIDs and identify associated factors including educational status, and health insurance coverage among the public in Gondar City, Ethiopia, to inform evidence-based public health interventions and regulatory policies. A community-based cross-sectional study design was employed among 786 residents from July 30 to August 30, 2023 to collect data on self-medication of NSAIDs. A structured interviewed questionnaire was used to gather information. All residents who were present at the time of data collection period were our study population. Prevalence of self-medication practice with NSAIDs were the primary outcome. A multivariable logistic regression was applied to identify factors associated with self-medication practices. The findings revealed the prevalence of self-medication with NSAIDs among the Gondar public is 69.2%.  Educational status, and current health insurance user were identified as predictors of NSAIDs self-medication practices. Pharmacist-led patient counseling, strict enforcement of over the counter NSAID sales regulations, and mandatory warning labels at retail pharmacies are needed to reduce inappropriate NSAID use and prevent adverse health outcomes.